Characterization of the water–titanium interaction and its effect on the adhesion of titanium-C/PEKK joints. (November 2022) - Marinosci, V.M.; Chu, L.; Grouve, W.J.B.; Wijskamp, S.; Akkerman, R.; de Rooij, M.B.
Abstract: This study investigates the mechanisms governing the degradation of co-consolidated titanium-C/PEKK interfaces. Atomic force microscopy was used to demonstrate that the titanium-oxide surface adsorbs moisture. Combined with the diffusion of water molecules through the composite tape material, this causes a severe deterioration of the co-consolidated titanium-C/PEKK interfacial toughness, as measured by means of a mandrel peel test on conditioned specimen. A partial recovery of the interfacial toughness after drying of the specimens indicates that the degradation is reversible, providing evidence that the interaction between titanium and C/PEKK is predominantly characterized by secondary bonds. Highlights: The water molecules diffuse through C/PEKK when exposing titanium-C/PEKK joints in hot-wet environment. The water molecules that reach the interface are majorly adsorbed by the titanium surface. The adsorbed water layer causes a drop of the fracture toughness of the titanium-C/PEKK interfaces. Titanium-C/PEKK bond degradation is reversible as the toughness recovers when re-drying the specimens. The toughness recovery is an indication that the titanium-C/PEKK adhesion relies on physical interactions.